Live and Let Dye: Visualizing the Cellular Compartments of the Malaria Parasite Plasmodium falciparum. Issue 7 (18th November 2019) - Linzke, Marleen; Yan, Sun Liu Rei; Tárnok, Attila; Ulrich, Henning; Groves, Matthew R.; Wrenger, Carsten
Abstract: Malaria remains one of the deadliest diseases worldwide and it is caused by the protozoan parasite Plasmodium spp . Parasite visualization is an important tool for the correct detection of malarial cases but also to understand its biology. Advances in visualization techniques promote new insights into the complex life cycle and biology of Plasmodium parasites. Live cell imaging by fluorescence microscopy or flow cytometry are the foundation of the visualization technique for malaria research. In this review, we present an overview of possibilities in live cell imaging of the malaria parasite. We discuss some of the state‐of‐the‐art techniques to visualize organelles and processes of the parasite and discuss limitation and advantages of each technique. © 2019 International Society for Advancement of Cytometry